Creation of a stable vector vortex beam with dual fractional orbital angular momentum - Lingyu Wang; Guanxue Wang; Xiangmei Dong; Xiumin Gao; Songlin Zhuang (Scientific Reports)
Abstract Recently, vortex beams have been widely studied and applied because they carry orbital angular momentum (OAM). It is widely acknowledged in the scientific community that fractional OAM does not typically exhibit stable propagation; notably, the notion of achieving stable propagation with dual-fractional OAM within a single optical vortex has been deemed impracticable. Here, we address the scientific problem through the combined modulation of phase and polarization, resulting in the generation of a dual-fractional OAM vector vortex beam that can stably exist in free space. Applying this unique characteristic, we derive an integrated analytical model to calculate the focused electromagnetic fields and Poynting vector distributions based on Debye vector diffraction integral. Utilizing phase stitching technology, this research combines two fractional topological charges to investigate the properties of dual-fractional OAM optical vortices with diverse polarization conditions. Furthermore, the transmission characteristics of these optical vortices are meticulously analyzed. This work not only enriches the types of vortex beams but also provides a novel optical tool, potentially transformative for applications in optical communications, optical manipulation, and optical imaging.